Chemosensory event-related potentials during sleep: a pilot study - Stuck, Boris; Weitz, Heike Astrid; Hörmann, Karl; Maurer, Joachim T.; Hummel, Thomas (Neuroscience letters, 2006)
Aim of the present pilot study was to investigate whether cortically generated chemosensory event-related potentials (ERPs) can be recorded during sleep. Chemosensory function during sleep was assessed in 14 healthy female volunteers. An overnight polysomnography was performed to assess nocturnal sleep and to classify sleep stages. Chemosensory ERPs were recorded using air-dilution olfactometry. H2S (4ppm) was used for olfactory and CO2 (40%, v/v) for trigeminal stimulation. Chemosensory ERPs could be recorded during sleep for both olfactory and trigeminal stimuli in some but not all subjects. Compared to baseline, latencies of olfactory ERPs were longer and amplitudes were larger during light sleep and slow wave sleep (SWS). For trigeminal stimulation N1 latencies were longest during REM sleep. These results indicate that both trigeminal and olfactory ERPs can be recorded during sleep suggesting that chemosensory stimuli are processed on a cortical level during sleep.
Gesehen am 11.03.2022